Comparative Susceptibility of Different Mouse Strains to Liver-Stage Infection With Plasmodium berghei Sporozoites Assessed Using In Vivo Imaging. (1st March 2017) - Li, Qigui; Xie, Lisa; Caridha, Diana; Roncal, Norma; Zeng, Qiang; Zhang, Jing; Zhang, Ping; Hickman, Mark; Read, Lisa
ABSTRACT: Background: The liver stages of Plasmodium parasites are important targets for the discovery and development of prophylactic drugs. Methods: A real-time in vivo imaging system was used to determine the level of luminescence measured from firefly luciferase expression by sporozoites developing in hepatocytes in different strains of mice. Results: The luminescence values (photon counts/sec) measured from the anatomical liver location in the untreated mice infected with 10, 000 Plasmodium berghei sporozoites were 8.15 × 10 5 for C57BL/6 Albino, 2.12 × 10 5 for C3H/HeNCrL, 0.91 × 10 5 for C57BL/6 WT, 0.28 × 10 5 for BALB/c, and 0.16 × 10 5 for ICR/CD-1 mice. This data suggests that the C57BL/6 Albino strain is most susceptible to luminescent photon, mainly because the less light scattering and absorption from deeper tissues and the skin in the strain of mouse. The photon count observed in black C57BL/6 wild type mice was shown to be 88.83% lower compared to C57BL/6 Albino mice. Although the highest growth rate of sporozoites in hepatocytes was found for C57BL/6 wild type mice in this study, the black skin of this mouse significantly reduced parasite-associated bioluminescence. Conclusions: The minimal light scattering and absorption and also enhanced susceptibility to liver infection of C57BL/6 Albino mice makes this strain preferable sensitivity for discovery and development of prophylactic antimalarial drugs.